Singapore Management University Report to Stakeholders 2016 - 2017 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
SMU has come a long way since we opened our doors to our first students in 2000. We have adapted and grown as we created and seized new opportunities. As a result, today we are blessed with a world-class campus in the heart of Singapore’s city centre, six schools offering both undergraduate and postgraduate programmes as well as many other postgraduate, professional and continuing education programmes; and close to 10,000 students on campus. All this was brought into focus this year as we opened the splendid new School of Law building, with its jewel-like Kwa Geok Choo Law Library and other outstanding facilities. We are indeed fortunate to have so fine a building in such a superb location. It is made possible by the solid support and great generosity of a number of donors as well as the foresight and beneficence of the Singapore authorities. However, it is also due to the hard work, diligence and sacrifices of many others in the SMU community. Fourteen cohorts of undergraduates and other alumni have proven themselves to be valuable members of society who are highly sought after by employers; our faculty members have proven themselves to be highly accomplished educators who also produce research that impacts the real world in positive ways; and the dedication and achievements of our staff have been recognised and awarded.